Pengaruh Pemberian Sayur Daun Kelor terhadap Peningkatan Kadar Hemoglobin - Rahwani; Ary Oktora Sri Rahayu; Komaria Susanti; Wira Ekdeni Aifa (Jurnal Kebidanan Harapan Ibu Pekalongan, 2026)
Moringa leaves are one of the plants rich in protein, vitamins, and iron. There are 450 mg of iron (Fe) in every kilogram of moringa leaves, which can be used to prevent various conditions such as low hemoglobin levels during pregnancy. This study aimed to determine the effect of giving moringa leaf vegetables on increasing hemoglobin levels in second- and third-trimester pregnant women in Karya Mukti Village, Rimba Melintang District, Rokan Hilir Regency. This was a quantitative study using a pre-experimental design with a one-group pretest-posttest design model. The study was conducted in Karya Mukti Village, Rimba Melintang District, Rokan Hilir Regency, in June and July 2025. The population in this study consisted of all second- and third-trimester pregnant women with low hemoglobin levels in Karya Mukti Village, with a sample size of 25 respondents. Data were analyzed using univariate and bivariate analysis with a dependent t-test. The results showed that the mean hemoglobin level before consuming moringa leaf vegetables was 9.876, and after consuming moringa leaf vegetables, the mean value increased to 10.952. There was an effect of giving moringa leaf vegetables on increasing hemoglobin levels in pregnant women in Karya Mukti Village, Rokan Hilir Regency (p = 0.000).